Long-Term Cognitive Outcomes and Sleep in Adults After Extracorporeal Life Support. (2nd April 2021) - Daou, Marietou; Lauzon, Claire; Bullen, E. Caroline; Telias, Irene; Fan, Eddy; Wilcox, M. Elizabeth
Abstract : Objectives: To assess differences in cognitive outcomes and sleep in adult survivors of critical illness, managed with venovenous extracorporeal membrane oxygenation as compared to conventional mechanical ventilation only. Design: Retrospective cohort study linked with data from the COGnitive outcomes and WELLness study. Setting: A multisite study from five adult medical/surgical ICUs in Toronto. Patients: Thirty-three ICU survivors including adult patients who received venovenous extracorporeal membrane oxygenation ( n = 11) matched with patients who received mechanical ventilation only ( n = 22) using specified covariates (e.g., age). Interventions: None. Measurements and Main Results: Baseline demographics and admission diagnoses were collected at enrollment. Cognitive outcome was evaluated using the Repeatable Battery for the Assessment of Neuropsychologic Status (global cognitive function) and Trail Making Test B (executive function), and sleep variables were estimated using actigraphy. Assessments occurred at 7 days post ICU discharge and again at 6- and 12-month follow-up. No statistically significant difference was seen between patients treated with or without venovenous extracorporeal membrane oxygenation in the mean daily Riker Sedation Agitation Score; however, patients in the venovenous extracorporeal membrane oxygenation group received greater amounts of fentanyl over their ICU stay as compared to patients receiving conventional mechanical ventilation only ( p < 0.001). No significant differences were found in performance on either of the cognitive assessment tools, between survivors treated or not with venovenous extracorporeal membrane oxygenation at any of the time points assessed. Total sleep time estimated by actigraphy increased from approximately 6.5 hours in hospital to 7.5 hours at 6-month follow-up in all patients, regardless of treatment type. Total sleep time remained consistent in both groups from 6 to 12 months post ICU discharge. Conclusions: In this small retrospective case series, no significant differences were found in sleep or cognitive outcomes between extracorporeal life support and non–extracorporeal life support survivors. Further, in this hypothesis-generating study, differences in administered sedative doses during the ICU stay seen between the two groups did not impact 6- or 12-month cognitive performance or actigraphy-estimated sleep time.